2013
DOI: 10.3389/fpsyg.2013.00759
|View full text |Cite
|
Sign up to set email alerts
|

Processing bimodal stimuli: integrality/separability of color and orientation

Abstract: We examined how two distinct stimulus features, orientation and color, interact as contributions to global stimulus dissimilarity. Five subjects rated dissimilarity between pairs of bars (N = 30) varying in color (four cardinal hues, plus white) and orientation (six angles at 30° intervals). An exploratory analysis with individual-differences multidimensional scaling (MDS) resulted in a 5D solution, with two dimensions required to accommodate the circular sequence of the angular attribute, and red-green, blue-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Here we consider that this alternative does not hold. Particularly, we used a thin line (1 pixel thick, 0.03°) to convey the value of width and height, which is a common and well-accepted manner in the research of length perception (e.g., Avery & Day, 1969;Brosvic & Cohen, 1988;Charras & Lupiáñez, 2009;Charras & Lupiáñez, 2010;Lipshits & McIntyre, 1999). Moreover, our post hoc interview suggested that no participants subjectively treated these lines as rectangles (see footnote 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we consider that this alternative does not hold. Particularly, we used a thin line (1 pixel thick, 0.03°) to convey the value of width and height, which is a common and well-accepted manner in the research of length perception (e.g., Avery & Day, 1969;Brosvic & Cohen, 1988;Charras & Lupiáñez, 2009;Charras & Lupiáñez, 2010;Lipshits & McIntyre, 1999). Moreover, our post hoc interview suggested that no participants subjectively treated these lines as rectangles (see footnote 2).…”
Section: Discussionmentioning
confidence: 99%
“…Stimuli composed of separable features have feature structures that are directly perceived; in other words, the feature structure itself determines the similarity between stimuli (a linear summation of the absolute differences each of the features in isolation; cf. Bimler, Izmailov, & Paramei, 2013). In contrast, integral dimensions are those that can be manipulated independently but not attended to and processed independently of each other, such as width and height, brightness and saturation, and hue and color saturation.…”
Section: Integral Features and Separable Featuresmentioning
confidence: 99%
“…Likewise, performance in contour integration was similar from either color or luminance local elements ( McIlhagga and Mullen, 1996 ; Rentzeperis and Kiper, 2010 ). Furthermore, recent rating experiments on the similarity of two bars varying in both orientation and color have been inconclusive on how separable color and orientation are ( Bimler et al, 2013 ). This evidence suggests the possibility of color and orientation mechanisms interacting at an early stage of visual processing.…”
Section: Behavioral Studiesmentioning
confidence: 99%
“…We computed, separately for each target type, simple Euclidean distances between each pair of the 44 BFI items with reverse-scored items for each trait keyed in the proper direction. A Euclidean distance measure conforms to the assumption that perceivers cognitively integrate the information from a series of Likert scale judgments into a coherent perception of a target (Bimler et al, 2013) and is frequently used in MDS studies in which objects are described by a series of rating scales (e.g., Hart et al, 1995; Hartwell & Kaplan, 2018; Kressel et al., 2012; Tiliopoulos et al., 2009; van Tilburg et al., 2018).…”
Section: Resultsmentioning
confidence: 99%